2019
DOI: 10.1111/vco.12556
|View full text |Cite
|
Sign up to set email alerts
|

Tumour‐infiltrating lymphocytes in canine melanocytic tumours: An investigation on the prognostic role of CD3+ and CD20+ lymphocytic populations

Abstract: The study of the immune response in several types of tumors has been rapidly increasing in recent years with the dual aim of understanding the relationship between neoplastic and immune cells as well as identifying targets for cancer immunotherapy. Despite being considered one of the most immunogenic tumor types, melanoma can progress in the presence of abundant lymphocytic infiltration, therefore suggesting that the immune response is not able to efficiently control tumor growth. The purpose of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 73 publications
3
38
0
Order By: Relevance
“…Our results are consistent with the expectation that the higher PD-1 expression in the study samples is contributed by the more abundant T cell population; confirmation of this conclusion awaits cellular localization when appropriate antibodies are available for IHC. Our findings of TILs in all 10 melanoma cases examined are consistent with those of other investigators 29 who reported the presence of TILs (as CD3 + and CD20 + cells) in a high percentage of melanomas (78.1% of oral cases and 64.7% of cutaneous cases). It should be noted that our melanoma group included both oral (16 cases) and cutaneous (6 cases) melanomas.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are consistent with the expectation that the higher PD-1 expression in the study samples is contributed by the more abundant T cell population; confirmation of this conclusion awaits cellular localization when appropriate antibodies are available for IHC. Our findings of TILs in all 10 melanoma cases examined are consistent with those of other investigators 29 who reported the presence of TILs (as CD3 + and CD20 + cells) in a high percentage of melanomas (78.1% of oral cases and 64.7% of cutaneous cases). It should be noted that our melanoma group included both oral (16 cases) and cutaneous (6 cases) melanomas.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, a relevance between TILs and hematologic parameters in breast cancer was demonstrated where LMR revealed significant correlation with CD8 + 51 . However, a previous study has shown that, despite tumour infiltrating lymphocytes have been described in most melanocytic tumours, lymphocytic infiltration is usually mild 52 . These data might be explained with high‐tumour mutational burden of melanoma and low expression of tumour‐associated antigens by neoplastic melanocytes.…”
Section: Discussionmentioning
confidence: 95%
“…The infiltration of these cells is important for the formation of immune response. Therefore, in melanoma, colorectal carcinoma or autoimmune diseases, CD3 positivity plays an important role in the diagnosis and the evaluation of treatment efficacy (Cimino et al, 2019;Porcellato et al, 2019;Taavela et al, 2019). In our study, it was remarkable that CD3þ lymphocytes decreased in the presence of BPA.…”
Section: Discussionmentioning
confidence: 55%
“…Likewise, CD20þ B lymphocyte infiltration is a determining factor in autoimmune diseases and cancer. The CD20 positivity and amount of CD20þ B lymphocyte are used to diagnose cancer (oral melanoma, oropharyngeal squamous cell carcinoma, Burkitt lymphoma) or various autoimmune diseases (multiple sclerosis, cardiomyopathy) (Chegni et al, 2019;Hladíková et al, 2019;Michel et al, 2019;Porcellato et al, 2019;Tschöpe et al, 2019). The expression of CD20 molecules was enhanced in malignant B lymphocytes (Chegni et al, 2019).…”
Section: Discussionmentioning
confidence: 99%